THE ROLE OF EARNINGS MANAGEMENT, CREDIT RISK, AND COST EFFICIENCY, MODERATED BY INTERNAL CONTROL, IN PREDICTING MARKET REACTIONS AT BANKS LISTED ON THE IDX - Caroline Tiofanny; Fahmi Natigor Nasution; Sirojuzilam Hasyim (PT. Radja Intercontinental Publishing, 2026)
This study examines the impact of earnings management, credit risk, and cost efficiency on market reaction, using internal supervision as a moderating variable. Focusing on the Indonesian banking sector, secondary data from 40 banking companies listed on the Indonesia Stock Exchange (IDX) were selected via purposive sampling. Variables were proxied by discretionary accruals (earnings management), Non-Performing Loans (credit risk), the BOPO ratio (cost efficiency), the proportion of independent commissioners (internal supervision), and abnormal returns (market reaction). Data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The results reveal that earnings management does not affect market reaction, indicating investors do not respond to earnings information indicating manipulation. Conversely, credit risk and cost efficiency significantly influence market reaction, reflecting investor focus on loan risk and operational management. Furthermore, while internal supervision does not moderate the effect of earnings management, it significantly moderates the impacts of both credit risk and cost efficiency. Ultimately, these findings highlight that effective corporate governance mechanisms, such as independent commissioners, enhance information credibility and market sensitivity to financial performance.